Age and sex-specific variations of vitamin D level in Bangladeshi population: a laboratory-based study - Maruf-Ur-Rahman, M.; Islam, M. Rafiqul; Begum, Wazeda; Islam, M. Shafiqul; Mubin, Nazirum; Golam Kibria, A. H. M. (International Journal of Research in Medical Sciences, 2025)
Background: In Bangladesh, vitamin D deficiency (VDD) is a silent epidemic that is neither recognized nor managed properly. The purpose of this research was to compare vitamin D levels across age groups and sexes in the population of Bangladesh. Methods: This was a laboratory-based retrospective study conducted in Dhaka, Bangladesh. Data on the age, gender, and vitamin D status of all 1074 people of all ages and both sexes who had their vitamin D levels checked at Ibn Sina D. Lab and Consultation Centre, Doyagonj, Dhaka, on a doctor’s recommendation were collected. Vitamin D levels (ng/ml) were categorized as deficiency (0 to <20), insufficiency (20-<30), sufficiency (30-100), and potential toxicity (>100). Participants were then divided into 0-10, >10-25, >25-50, and >50 years age group. Results: The participants’ average age was 29.15±20.32 years, with the majority (39.5%) being over 25-50 years old. Nearly two-thirds [702 (65.4%)] of the participants were female. Participants aged 0-10, >10-25, >25-50, and >50 years had mean vitamin D levels of 26.68±20.30, 16.47±7.18, 20.30±9.35, and 22.73±13.55 ng/ml, respectively. The participants' average vitamin D levels varied dramatically with age. Among the subjects, 605 (56.3%) were vitamin D deficient (95% confidence interval: 53.4-59.1). VDD was detected in 52.2% of males and 58.5% of females, indicating that females are significantly more affected. Conclusions: VDD is extremely common among Bangladeshi people. It is more prevalent among young and females. Ensuring proper nutritional supplementation among at-risk groups can help to prevent the long-term negative health consequences of VDD.